Temperature Dependence of Shear Elasticity of Some Liquids - Budaevl, Ochir R; Damdinovl, Bair B; Adiyasuren, P; Tsend-Ayush, A (Proceedings of the Mongolian Academy of Sciences, 2011)
The temperature dependencies of real and imaginary parts of complex shear modulus of liquids have been obtained. It has shown that both real shear modulus G’ and ft imaginary shear modulus G” decrease with increasing temperature. The experiments have been carried out by resonance method at a shear oscillation frequency of 74 kHz. Liquids of viscosity 0.02 - 0.03 Pa-s have been investigated. DOI: http://dx.doi.org/10.5564/pmas.v0i4.47 Proceedings of the Mongolian Academy of Sciences 2009 No 4 pp.59-63